SPECIES DIVERSITY OF THE EPIBENTHOS IN A HIGHLY DISTURBED CORAL REEF COMMUNITY IN THE PHILIPPINES - Gomez, Edgardo D. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1977)
Baseline studies on the marine benthic communities around the proposed site of the first nuclear power plant in the Philippines have indicated a highly disturbed coral reef community. The areas studied are all subtidal, mostly starting just below the littoral and having an average depth of five meters. The study consisted in taking a census with SCUBA of the epibiota in quadrats on transects laid out perpendicular to the shoreline. Results of the sampling during the dry season indicate a predominantly algal (Padina) community of low species diversity. Many of the conspicuous components of Philippine coral reefs are either absent or are present only in small numbers, e.g., hard and soft corals, crinoids, tridacnids, and colorful serpulids. Dynamite fishing is no doubt a major factor responsible for the condition of the dead reefs. Weather and erosion of the land areas with the resulting siltation have probably contributed to the poor condition of the reef communities as well.